Nutrient and organic matter removal from low strength sewage treated with constructed wetlands. Issue 1 (2nd January 2019) - Mello, D.; Carvalho, K. Q.; Passig, F. H.; Freire, F. B.; Borges, A. C.; Lima, M. X.; Marcelino, G. R.
ABSTRACT: The role of Eichhornia crassipes for removing pollutants from low strength sewage was evaluated in three pilot-scale constructed wetlands (CW): CW 1, planted with E. crassipes in a filter media; CW 2, unplanted, composed by filter media; and CW 3, composed by E. crassipes floating on the sewage. The operation was divided into three stages by varying the nominal hydraulic retention time into: (I) 24 h; (II) 48 h; (III) 72 h. Temporal sampling profiles were carried out with collection of the influent and effluent samples to determine temperature, pH, chemical oxygen demand (COD), TKN and TP. Contents of TP and TN were analyzed in the plant tissue of the macrophyte. The best removal efficiency rates for phosphorus (38%) and TKN (47%) were obtained in CW 3 for 72 h. The highest COD removal was observed in the CW 2 (80%) for 48 h. The macrophyte E. crassipes contributed to the absorption process with uptake rate percentages of 8.3% (CW 1) and 9.0% (CW 3) for TN and 0.78% (CW 1) and 1.56% (CW 3) for TP on the dry matter of the plant. The chosen species planted in the systems contributed to the achievement of higher nutrient removal.